Educação inclusiva: Por um devir minoritário em uma escola para todos - Andrade, Valéria Silva Freire de (2007)
This essay aims at understanding the constitution of the inclusive school in its relations with the social, political and economic forces which traverse and integrate it, as well as investigate possibilities of production of new forms of subjectiveness ensued by this proposal. Herein the educational environment is taken in its paradoxal dimension, once it is a privileged medium for the production and invention of thoughts and ways of learning and living, but also for the reproduction and repression of forms of thinking and existing. Once embedded in this context, the inclusive school bears all the paradoxes and conflicts caused by and resulting in the oscillation of forces which influence the processes of subjectivenesss in contemporary society. Thus, some of the entrapments which operate in the constitution of the inclusive school with the intention of maintaining classificatory and discriminatory forms existing in education and society as well as possibilities of resisting excluding and segregating forms brought by this proposal are shown herein. In order to do that, this essay conjugates the cartographic method with the thought of authors in consonance with the Philosophy of Difference. Thus, statements of people involved in the inclusion proposal, observational extracts from my field work journal, Deleuze s claims on minor literature transferred to the educational field and the concept of vibrational body concocted by Suely Rolnik have been used, among others. Finally, the axis which directs the constitution of the inclusive school a school for all- as a powerful principle in the sense of awakening a minor becoming (devir) in schools while dissolving the dualisms and conflicts which exist in notions of normal/ abnormal, man/ woman, black/ white, included/ excluded, is affirmed